Evaluation of four gridded climate products for streamflow and drought simulations in the Kelantan River Basin, Malaysia - Hongrong Du; Mou Leong Tan; Kwok Pan Chun; Fei Zhang (Geocarto International)
Gridded climate products (GCPs) play a vital role in hydro-climatic modeling by overcoming the limitations of gauge data. This study compares the performance of the recently launched NASA POWER and ERA5-Land, with CHIRPS and APHRODITE, in simulating streamflow and drought from 1985 to 2015 in the Kelantan River Basin, Malaysia. When the SWAT+ model was incorporated with the original GCPs, APHRODITE demonstrated the best performance in monthly streamflow simulations, achieving Nash-Sutcliffe Efficiency (NSE) values from 0.61 to 0.71 and coefficient of determination (R2) values from 0.74 to 0.76, outperformed other GCPs. Bias correction further improved the performance of GCPs in simulating streamflow. Additionally, the SWAT+ model performed slightly better when GCPs were combined with temperature data from NASA POWER compared to ERA5. Most GCPs effectively identified drought events in 1998, 2005, 2010, 2014, and 2015 under SPI-1 and SPI-3, but the intensity of dryness varied slightly among the products.